Rebound Syndrome in Patients With Multiple Sclerosis After Cessation of Fingolimod Treatment - Hatcher, Stacy Ellen; Waubant, Emmanuelle; Nourbakhsh, Bardia; Crabtree-Hartman, Elizabeth; Graves, Jennifer S (JAMA neurology, 2016)
The appropriate sequencing of agents with strong immune system effects has become increasingly important. Transitions require careful balance between safety and protection against relapse. The cases presented herein highlight that rebound events after ceasing fingolimod treatment may happen even with short washout periods (4 weeks) and may perpetuate despite steroid treatment or the immediate use of fast-acting immune therapies, such as rituximab. To describe rebound syndrome in patients with multiple sclerosis (MS) after cessation of fingolimod treatment. Clinical and demographic data were extracted from electronic medical records from the University of California, San Francisco, Multiple Sclerosis Center from January 2014 to December 2015. Magnetic resonance images were reviewed by MS neurologists (J.S.G., E.W., B.N., and E.C.H.). Rebound syndrome was defined as new severe neurological symptoms after ceasing fingolimod treatment, with the development of multiple new or enhancing lesions exceeding baseline activity. We reviewed the PubMed database from January 2010 to December 2015 for similar cases of severe disease reactivation after ceasing fingolimod treatment using search terms fingolimod and either rebound or reactivation. Participants were included if they stopped receiving fingolimod between January 2014 and December 2015. Five patients were identified who experienced rebound after ceasing fingolimod treatment. Each patient received treatment with oral fingolimod for various durations. Occurrence of rebound after ceasing fingolimod treatment. The mean (SD) age of the 5 female patients presented in this case series was 35.2 (6.4) years. Of the 46 patients that stopped fingolimod treatment within the 2-year period, 5 (10.9%) experienced severe relapse 4 to 16 weeks after ceasing fingolimod treatment. Despite varying prior severity of relapsing-remitting course, all participants experienced unexpectedly severe clinical relapses accompanied by drastic increases in new or enhancing lesions seen on magnetic resonance imaging evidenced by a median (range) increase of 9 (0->30) new gadolinium-enhancing lesions and a median (range) of 9 (0->30) new T2 lesions. New lesion development persisted for 3 to 6 months despite treatment with corticosteroids (n = 3) and initiation of B-cell depleting therapy (n = 2). In addition, 11 patients were identified through literature review reported as having severe relapses consistent with a rebound syndrome and similar features to our 5 cases. These cases provide evidence for a fingolimod rebound syndrome at a clinically relevant frequency, highlighting the need to determine the best methods for sequencing or discontinuing MS therapies. A large prospective registry or population-based study would be helpful to confirm this rebound phenomenon and to determine contributing factors, including immune biomarkers, that increase risk for this syndrome.